PENGARUH KEPUASAN KERJA DAN KOMPENSASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA KANTOR KECAMATAN DI WILAYAH BARAT KABUPATEN ACEH UTARA - Misbahuddin Misbahuddin; Mohd Heikal; Naufal Bachri (Universitas Malikussaleh, 2021)
This study aims to determine the effect of job satisfaction and compensation on organizational commitment and job satisfaction, compensation and organizational commitment to organizational citizenship behavior and organizational commitment to mediate the relationship between job satisfaction and compensation on organizational citizenship behavior. The data used in this study are primary data of 135 respondents at the District office in the West Region of North Aceh Regency. The data analysis method in this study uses a structural equation model with the help of analysis of moment structure. The results of the study found that job satisfaction has a positive and significant effect on organizational commitment. Meanwhile, compensation has no effect on organizational commitment. Another finding is that organizational commitment and job satisfaction have a positive and significant effect on organizational citizenship behavior. Furthermore, compensation has a negative and significant effect on organizational citizenship behavior. Organizational commitment fully mediates the effect of job satisfaction on organizational citizenship behavior, but organizational commitment does not mediate the relationship between compensation and organizational citizenship behavior.